Regenerative capacity of trophoblast stem cell-derived extracellular vesicles on mesenchymal stem cells - Yoon-Young Go; Chan-mi Lee; Sung-Won Chae; Jae-Jun Song (Biomaterials Research, 2023)
Abstract Background Human mesenchymal stem cells (MSCs) are therapeutic for clinical applications because of their excellent immunomodulatory and multiple lineage differentiation abilities at tissue injury sites. However, insufficient number of cells and lack of regenerative properties during in vitro expansion still limit the clinical applicability of MSC therapies. Here, we demonstrated a preconditioning strategy with trophoblast stem cell-derived extracellular vesicles (TSC-EVs) to boost the proliferation and regenerative capacity of MSCs. Methods We employed cell proliferation analyses such as CCK8 and BrdU assays to determine the proliferation-promoting role of TSC-EVs on MSCs. Osteogenic effects of TSC-EVs on MSCs were assessed by alkaline phosphatase (ALP) activity, calcium assays, and calvarial bone defect animal models. For skin regenerative effects, skin wound mice model was exploited to analyze wound-healing rate in this study, as well as immunofluorescence and histological staining evaluates. We also performed the small RNA profiling and RNA-sequencing analyzes to understand the cellular mechanism of TSC-EVs on MSCs. Results TSC-EVs significantly promoted MSC proliferation under xeno-free conditions and facilitated the therapeutic effects of MSCs, including osteogenesis, anti-senescence, and wound healing. Transcriptomic analysis also provided evidence that specific microRNAs in TSC-EVs and differentially expressed genes (DEGs) in TSC-EV-treated MSCs showed the possibility of TSC-EVs triggering the regenerative abilities of MSCs with cytokine interaction. Hence, we found that NGF/Akt signaling mediated the regenerative effects of TSC-EVs on MSCs as a particular cellular signaling pathway. Conclusion The results of this study demonstrated the functional properties of TSC-EVs on MSCs for MSC-based therapeutic applications, suggesting that TSC-EVs may serve as a potential preconditioning source for MSC therapy in the clinical field of regenerative medicine. Graphical abstract